2017
DOI: 10.18632/oncotarget.15971
|View full text |Cite
|
Sign up to set email alerts
|

Targeting HOX/PBX dimers in cancer

Abstract: The HOX and PBX gene families encode transcription factors that have key roles in establishing the identity of cells and tissues in early development. Over the last 20 years it has become apparent that they are also dysregulated in a wide range of solid and haematological malignancies and have a predominantly pro-oncogenic function. A key mode of transcriptional regulation by HOX and PBX proteins is through their interaction as a heterodimer or larger complex that enhances their binding affinity and specificit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(80 citation statements)
references
References 91 publications
1
79
0
Order By: Relevance
“…Similar results were obtained for KYSE70, KYSE150 and KYSE450 cell lines (Figure C). Previous studies have suggested that upregulation of c‐fos could trigger apoptosis . c‐fos showed significant upregulation in HXR9‐treated KYSE70 and KYSE450.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Similar results were obtained for KYSE70, KYSE150 and KYSE450 cell lines (Figure C). Previous studies have suggested that upregulation of c‐fos could trigger apoptosis . c‐fos showed significant upregulation in HXR9‐treated KYSE70 and KYSE450.…”
Section: Resultsmentioning
confidence: 87%
“…Previously, it was shown that a synthetic peptide known as HXR9 was capable of blocking the interaction between HOX and PBX proteins both in vitro and in vivo. HXR9 functioned as a competitive antagonist of the interaction by mimicking the conserved hexapeptide region . The present study aimed to investigate whether HXR9 could block the interaction between multiple HOX members (HOXB7, HOXC6, HOXC8) and PBX in ESCC cells and inhibit their oncogenic functions.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of the former include HOXA5, which can promote expression of the p53 tumor suppressor protein [21] , and HOXC12, which promotes cellular differentiation in follicular lymphoma [22] . However, the majority of reports indicate that HOX genes have a pro-oncogenic role, including functions that support tumor growth and invasion such as angiogenesis, metastasis, and immune evasion [23] . At the cellular level, a generalized role for many HOX proteins in cancer appears to be to prevent apoptosis by inhibiting cFos [24][25][26][27] and dual specificity protease 1 (DUSP1) expression [26,28,29] .…”
Section: The Hox Genesmentioning
confidence: 99%
“…Of these 4 HOX genes, HOXC6 is reported to be the most highly upregulated in primary, metastasized, and castrate-resistant prostate cancer, and the presence of HOXC6 RNA in urine might be a diagnostic marker for prostate cancer and a potential monitoring tool for disease progression [40] , and was shown to distinguish between high and low grade prostate tumors with a very high specificity when used in conjugation with a second urinary marker, DLX1 [41] . In addition, disrupting the interaction between HOX proteins and their PBX cofactor using the competitive antagonist HXR9 [23] causes apoptotic cell death in the prostate cancerderived cell lines LnCaP, DU145, and PC3, and was shown to block the growth of PC3 tumors in a mouse xenograft model [25] .…”
Section: Hox Genes In Prostate Cancermentioning
confidence: 99%
“…HOX members have previously been studied to regulate differentiation, proliferation, apoptosis, motility and angiogenesis . It has been shown that different HOX members are dysregulated (up‐regulated or down‐regulated) in various cancers, such as leukaemia, melanoma, breast cancer and ovarian cancer . HOXB8, a member of HOX family, is frequently expressed in ovarian serous carcinoma and associated with shorter survival in metastatic serous carcinoma .…”
Section: Introductionmentioning
confidence: 99%